A Meta-Analysis of UTAUT in the Sports Field - Taejung Kim (Korea Institute of Sport Science, 2023)
PURPOSE The purpose of this study was to analyze the effect size of the unified theory of acceptance and use of technology (UTAUT) in the sports field using a meta-analysis. METHODS After identifying related studies by using RISS, 22 articles were selected and used to analyze the relationship between UTAUT sub-factors (performance expectancy [PE], effort expectancy [EE], social influence [SI], and facilitating conditions [FC]) and intention to use via the comprehensive meta-analysis program. RESULTS The results are as follows: First, the effect size between PE and intention to use was 0.521. Second, the effect size between FC and intention to use was 0.514. Third, the effect size between EE and intention to use was 0.500. Finally, the effect size between SI and intention to use was 0.475. CONCLUSIONS Diverse strategies can be derived to increase consumers' intention to use in the sports field using the UTAUT model.